2008
DOI: 10.3748/wjg.14.1112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viral load on T-lymphocyte failure in patients with chronic hepatitis B

Abstract: AIM:To investigate peripheral T-lymphocyte subpopulation profile and its correlation with hepatitis B virus (HBV) replication in patients with chronic hepatitis B (CHB). METHODS:Distribution of T-lymphocyte subpopulations in peripheral blood was measured by flow cytometry in 206 CHB patients. HBV markers were detected with ELISA. Serum HBV DNA load was assessed with quantitative real-time polymerase chain reaction (PCR). The relationship between HBV replication and variation in peripheral T-cell subsets was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
2
18
2
1
Order By: Relevance
“…Chronic hepatitis B is responsible for the death of millions of people all over the world. Many studies have shown that cellular immune response against HBV virus is important in controlling the infection with this virus [Lavanchy, ; You et al, ]. T lymphocytes subgroups such as CD4 + and CD8 + cells are known to respond to this virus and directly affect on the severity of chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic hepatitis B is responsible for the death of millions of people all over the world. Many studies have shown that cellular immune response against HBV virus is important in controlling the infection with this virus [Lavanchy, ; You et al, ]. T lymphocytes subgroups such as CD4 + and CD8 + cells are known to respond to this virus and directly affect on the severity of chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators suggested the chronicity of HBV infection was caused by a deficient cellular immune function [Michalak et al, ; Khettry et al, ; Tülek et al, ]. Thus, T‐cell dysfunction might contribute towards viral persistence [You et al, ]. A significant decreasing trend in CD3 + and CD4 + cells and CD4 + /CD8 + ratio with increasing severity of hepatocyte damage with advancing age has been observed during HBV infection [You et al, ; Salih et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, approximately 780,000 people live with HIV; 26,000 died from Acquired Immune Deficiency Syndrome (AIDS) in 2009 [1], while 4.5 million Chinese have been infected with active pulmonary TB, 1.5 million of whom are smear-positive [2]; meanwhile 120 million people have been chronically infected with HBV [3], and more than 300,000 people die from HBV-related diseases every year [4]. According to the 6 th national population census, over 0.67 billion people live in rural areas and account for 50.32% of the entire population.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, efforts are under way to determine the effects of chronic HBV infection on the function of the peripheral immune system. A study involving 206 individuals with chronic HBV infection demonstrated that T-cell dysfunction in these individuals was extensive and persisted with a significant decrease in CD3 + T cells, which translated into a loss of competent cells that were immunologically capable of challenging the infection [79]. In fact, there have been reports that antiviral treatment can increase CD4 + [80] and CD8 + [81, 82] T-cell responsiveness to chronic HBV infection, suggesting that these cell populations were present but suppressed by HBV infection.…”
Section: Introductionmentioning
confidence: 99%